2019
DOI: 10.1029/2019jd030492
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonsoon Precipitation Dominates Groundwater Recharge Beneath a Monsoon‐Affected Glacier in Tibetan Plateau

Abstract: Groundwater recharge is poorly understood beneath the glacier due to the complex sampling conditions, although it is sensitive to the global change. Here we carried out the sampling and isotopic analysis on groundwater, ice‐melt water, river, and precipitation through a hydrological year at the lowest glacier of Mingyong in Hengduan Mountains, Southeastern Tibetan Plateau. The precipitation during the monsoon seasons (Pm) are more depleted in heavy isotopes than precipitation during the nonmonsoon seasons (Pnm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 71 publications
3
19
0
Order By: Relevance
“…Second, the isotopic composition of precipitation may provide useful information on water cycle processes in a perspective of water resource management. For example, the isotopic variability of precipitation at short time scales needs to be understood when using isotope‐based hydrograph separation to identify the different contributions to runoff and streamflow, or when using isotope‐based methods to understand groundwater recharge processes (Cui & Li, 2015; Kong, Wang, Pu, et al, 2019; Pu et al, 2017; Wang et al, 2018). Third, isotopic records of precipitation are used for paleo‐altitude reconstructions of the TP (Rowley & Currie, 2006; Rowley, 2007; Rowley & Garzione, 2007), based on the observed depletion of precipitation with altitude at present (Dansgaard, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the isotopic composition of precipitation may provide useful information on water cycle processes in a perspective of water resource management. For example, the isotopic variability of precipitation at short time scales needs to be understood when using isotope‐based hydrograph separation to identify the different contributions to runoff and streamflow, or when using isotope‐based methods to understand groundwater recharge processes (Cui & Li, 2015; Kong, Wang, Pu, et al, 2019; Pu et al, 2017; Wang et al, 2018). Third, isotopic records of precipitation are used for paleo‐altitude reconstructions of the TP (Rowley & Currie, 2006; Rowley, 2007; Rowley & Garzione, 2007), based on the observed depletion of precipitation with altitude at present (Dansgaard, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…However, the climatic information may be smoothed by melt flow in ice cores sampled from temperate glaciers, which usually have high melting rates (He et al, 2002). It has been illustrated that melting‐refreezing processes benefit the transformation of the temperate glaciers (Kong et al, 2019; Shi et al, 2008). Better understanding of the modifications of the isotopic signatures during snow melting would be the first step in comprehensive understanding of ice cores from temperate glaciers.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that snow meltwater differs isotopically from liquid precipitation, snow, and other water bodies of hydrological systems (Hürkamp et al, 2019; Lee et al, 2010; Moser & Stichler, 1974; Stichler et al, 2001). Consequently, knowing the isotopic composition of snow meltwater provides the possibility of estimating the contribution of snow meltwater to runoff (Laudon et al, 2002, 2004; Pu et al, 2017; Pu, He, Zhang, et al, 2013; Pu, He, Zhu, et al, 2013; Rodhe, 1981), identifying the recharge of snow meltwater to groundwater (Earman et al, 2006; Jasechko et al, 2017; Kong et al, 2019), or tracing the hydrological processes in snow‐covered basins (Ala‐aho et al, 2017). There are, however, multiple factors that influence the isotopic composition of snow meltwater, such as the melting process, evaporation/sublimation, refreezing, and dispersion (Evans et al, 2016; Laepple et al, 2018; Ritter et al, 2016; Stichler et al, 2001), which all need to be taken into account if snowmelt isotopes are used as a hydrologic tracer.…”
Section: Introductionmentioning
confidence: 99%
“…The metric chosen for this service is m 3 •year −1 , that is, the volume of freshwater recharged to the groundwater. The data of percentage of precipitation charging groundwater was collected from the literature where the results show that an average groundwater recharge volume is approximately 20% of the precipitation in the Yangtze Delta Region [43,44]. The perennial mean precipitation in the Zhangxi catchment ranges from 1341 mm to 1961 mm, with an average of 1480 mm.…”
Section: Freshwater Storage and Supplymentioning
confidence: 99%